GEORCC recommendations on target volumes in radiotherapy for Head Neck Cancer of Unkown Primary. (October 2018) - Cabrera Rodríguez, Joaquín; Cacicedo, Jon; Giralt, Jordi; García Miragall, Enrique; Lloret, Marta; Arias, Fernando; González Ruiz, María Angeles; Contreras, Jorge
Highlights: Review of series of patients with Head and Neck Cancer of Unknown Primary (HNCUP) treated with updated radiotherapy. We found that current HNCUP series have an specific pattern of relapse, either nodal as mucosal that differs from older series. The role of HPV infection and its management in HNCUP is emerging. A guideline for CTV definition in patients with HNCUP treated with modern radiotherapy (adjuvant or radical) is provided. Abstract: Head Neck Cancer of Unknown Primary (HNCUP) is a rare condition, representing approximately 5–10% of all head neck cancers. Radiotherapy, adjuvant or radical, is usually employed in the treatment of those patients. To date, no specific guidelines for the optimal definition of the target volume to be irradiated have been published. In recent years, there have been advances in the knowledge of the molecular biology of HNCUP, its diagnostic imaging and the implementation of sophisticated radiotherapy techniques with enhanced precision in target localization and treatment delivery. These progresses have provided valuable information about the natural history of HNCUP that will allow for establishment of the best treatment for each patient, including standardized, consistent and reproducible target volumes definitions. Several recommendations regarding how to choose volumes when contouring HNCUP in clinical practice are reported, in order to achieve a high rate of loco-regional control while avoiding unnecessary toxicity.